High-brightness CEP-stable light source with coverage from 340 nm to 40,000 nm - Elu, U.; Maidment, L.; Vamos, L.; Tani, F.; Novoa, D.; Frosz, M. H.; Badikov, V.; Badikov, D.; Petrov, V.; St Russell, P. J.; Biegert, J. (Optics InfoBase Conference Papers, 2022)
A mid-IR OPCPA comb source delivers a high-brightness coherent spectrum with coverage across 7 optical octaves, from the UV (340 nm) into the THz (40,000 nm).
CRIS-Team Scopus Importer:2022-09-02